Young and Sexual in Norway and Croatia: Revisiting the Scandinavian vs. Mediterranean Gendered Pattern of Sexual Initiation - Traen, Bente; Landripet, Ivan; Štulhofer, Aleksandar (2011)
This article describes and analyzes patterns of first sexual intercourse and contraception use from a bicultural perspective. Study results are based on a 2009–2010 large-scale national probability survey of young adults aged 18 to 24 years in Croatia (n = 1, 005) and Norway (n = 871). The findings corroborated the persistence of the dual model of sexual initiation in Europe (Scandinavian vs. Mediterranean), in which Norwegian women and Croatian men reported coital debut at an earlier age than their gender counterparts. Age difference between partners and the prevalence of condom use at first coitus were similar in both countries, with differences in contraceptive choices emerging with time. Young Norwegian men and women switched from using condoms to hormonal contraception when having been coitally active for some time. Interestingly, “the pill” remains rather unpopular among young Croatian women. Controlling for selected variables, using a condom at most recent sexual intercourse was significantly associated with condom use at first intercourse in all groups except Norwegian men, as well as with years of coital activity (except among Croatian men). Additionally, the odds of a condom being used at most recent intercourse were significantly correlated with same-sex sexual experience (only among Norwegian men) and with reporting the most recent intercourse with a casual partner (only among Norwegian participants). Country-specific patterns of contraceptive use are discussed in the context of public health and prevention.
Projekt MZOS
ENG